Comparative Studies of N-Glycans and Glycosaminoglycans Present in SIRC (Statens Seruminstitut Rabbit Cornea) Cells and Corneal Epithelial Cells from Rabbit Eyes. (July 2014) - Iwatsuka, Kinya; Iwamoto, Hiroki; Kinoshita, Mitsuhiro; Inada, Katsuhiro; Yasueda, Shin-ichi; Kakehi, Kazuaki
ABSTRACT Purpose: We compared cultured Statens Seruminstitut rabbit cornea (SIRC) cells and corneal epithelial cells from rabbit eyes by analyzing their N-glycans and glycosaminoglycans (GAGs). This work is a fundamental study on the efficacy of using cultured cells instead of animals for drug development. Materials and methods: N-Glycans and GAGs from SIRC cell monolayers and corneal epithelial cells of rabbit eyes were analyzed by capillary electrophoresis (CE) and a combination of high-performance liquid chromatography (HPLC) and mass spectrometry. Results: High mannose-type glycans and a hybrid-type glycan were the common N-glycans in SIRC cells and corneal epithelial cells of rabbit eyes. Mono-fucosylated biantennary glycans with or without one N-acetylneuraminic acid residue were observed only in SIRC cells. Hyaluronic acid was the only measurable GAG in the corneal epithelial cells of rabbit eyes. In contrast, hyaluronic acid and chondroitin sulfates were abundantly present in SIRC cells. Conclusions: Profiles of both N-glycans and GAGs were conspicuously different between SIRC cells and corneal epithelial cells of rabbit eyes. This report will be useful for the evaluation of pharmaceutical candidates when animals or cultured cells are employed in drug development studies.